Revolutionizing Cardiac Care: A Systematic Review Of Intelligent Wearables And Cloud-Based Analytics - Govindarajan, Vijay; Devi, Hansa; Kumar, Pawan (Biological and Clinical Sciences Research Journal, 2025)
Cardiovascular diseases (CVDs) continue to be the number one cause of global mortality and thus need innovative and scalable monitoring solutions. Smart wearable devices and cloud-based analytics have recently allowed remote, real-time cardiac monitoring that increases diagnosis lead times and decreases treatment cycle times. Objective: In this systematic review, we aimed to summarize the clinical effectiveness, technological strengths and weaknesses of intelligent wearables and cloud-integrated systems in cardiac care. Methods: With the use of PRISMA 2020 guidelines, we searched PubMed, Google Scholar and IEEE Xplore for articles with titles and abstracts between 2017 and 2025. We identified data for types of devices, measured parameters, clinical outcomes and integration with analytics platforms from the structured abstracts and their elements. Results: The analysis of 21 studies has been presented. ECG patches, smartwatches and biosensor textiles had very high sensitivity to detect arrhythmias, heart failure signs and ECG modifications, respectively, for the detection of wearables. Researchers were able to conduct real-time analytics, predictive modeling with AI and link to electronic health records using the cloud-based platform. Clinical outcomes included HAP decreases hospitalization rates and improved treatment adherence early intervention. But hurdles like data privacy, interoperability and patient engagement still loom. Conclusion: Intelligent wearables with Cloud based analytics will revolutionize cardiac care and allow for remote monitoring using continuous data-driven decision making. However, the standardization and long-term effects must be tested before wide-scale clinical implementation is possible.